TI_GERICHTE 12.2016.9 vom 11. April 2017 , Tutela giurisdizionale nei casi manifesti. Prelievero di averi bancari - TI Tribunale d'appello (2017)
Tutela giurisdizionale nei casi manifesti. Prelievero di averi bancari